DUODENAL WEBS: AN EXPERIENCE WITH 18 PATIENTS - Yogesh Kumar Sarin; Akshay Sharma; Shalini Sinha; Vidyanand Pramod Deshpande (EL-Med-Pub, 2012)
Aim: To describe the management and outcome of patients with duodenal webs, managed over a period of 12 ½ years in our unit.Methods: It is a retrospective case series of 18 patients with congenital duodenal webs, managed in our unit, between 1999 and 2011. The medical record of these patients was retrieved and analyzed for demographic details, clinical presentation, associated anomalies, and outcome. Results: The median age of presentation was 8 days (range 1 day to 1.5 years). Antenatal diagnosis was made in only 2 (11.1%) patients. The commonest presentation was bilious vomiting. Associated anomalies were present in 8/18 patients, common being malrotation of gut. Down's syndrome was seen in 2 patients and congenital heart disease in 1 patient. One patient had double duodenal webs. There was a delay in presentation of more than 5 days of life in 11/18 (61%) patients. Three patients who presented beyond neonatal age group had fenestrated duodenal membranes causing partial obstruction. In addition, the diagnosis was missed in patients operated for malrotation elsewhere (n=2), imperforate anus (n=2) and esophageal atresia with tracheo-esophageal fistula (n=1). A lateral duodenotomy with excision of the obstructive membrane was done in all patients. A trans-anastomotic tube (TAT) for enteral feeding was used in 8 patients The mortality rate was 4/18 (22%); the main causes being sepsis, prematurity, very low birth weight and associated congenital anomalies. The mean hospital stay for the 14 survivors was 18 days. Total parental nutrition (TPN) was not given to any patient.Conclusions: Congenital duodenal webs are different as the diagnosis is often missed especially in case of perforated webs. Outcome depends upon the time of presentation and associated anomalies. The use of TAT feeding for nutritional support is an easy alternative to TPN.